Optimasi Kinerja Balai Penelitian Dan Pengembangan Lingkungan Hidup Dan Kehutanan Aek Nauli Di Sumatera Utara - Henry Elvin Simamora; Manuntun Parulian Hutagaol; Irdika Mansur (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2024)
ABSTRACT The Aek Nauli Environment and Forestry Research and Development Center (BP2LHK Aek Nauli) has a relatively high budget absorption rate, averaging 96.96% from 2012 to 2016. However, this high budget absorption rate does not necessarily imply that the performance and budget management at BP2LHK Aek Nauli are perfect. Issues such as expenditure accumulation at the end of the year and discrepancies between planned and actual budget absorption on a monthly basis still persist. This study aims to recommend performance improvement strategies for the Aek Nauli Environmental and Forestry Research and Development Center using the SWOT method. The research results identified 10 strategies to enhance performance at BP2LHK Aek Nauli, including (1) Improving commitment to adhere to previously created documents, (2) Enhancing communication for rapid information dissemination related to the latest regulations, (3) Increasing routine evaluation and internal supervision to enhance compliance with regulations, (4) Allocating Non-Tax Revenue Budget (PNBP) to programs linked to seasonal variations, (5) Creating alternative budget arrangements, (6) Improving the quality of human resources to understand performance measurement processes, (7) Enhancing communication among employees regarding service, performance, and performance measurement, (8) Formulating activities aligned with the vision and mission, resulting in excellent public service, (9) Improving cooperation for utilizing research results with local stakeholders, and (10) Enhancing the dissemination of research findings. Keywords: BP2LHK, Budget Absorption, Strategy, SWOT